(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Kya Kya, known as Kembang Jepun, has transitioned from a predominantly Chinese cultural hub to a diverse economic and social space reflecting Indonesia’s multicultural identity. Using data collected from 130 signs across the district, combined with interview, this research examines language usage categorized as monolingual, bilingual, and multilingual, shedding light on the motives behind language selection. As a result, Indonesian emerges as the dominant language across all categories, reflecting its role as the national language. However, other languages such as Chinese, English, Dutch, and Javanese contribute to the district’s linguistic diversity. Bilingual signage highlights the coexistence of globalization and the enduring presence of the Chinese community, while multilingual signs underline the area’s multicultural identity. This study demonstrates how language in public spaces reflects Kya Kya’s evolving identity, shaped by historical legacies, cultural interactions, and social transformations. The findings provide valuable insights into the linguistic landscape of Surabaya and its relevance to broader discussions on language, culture, and urban identity in Indonesia.